Indonesia - Country Procurement Assessment Report : Reforming the Public Procurement System - World Bank (Washington, DC, 2013)
The main objectives of the Country Procurement Assessment Review (CPAR) are to diagnose the public procurement system in Indonesia, assess actual compliance with the country's procurement laws and regulations on the ground, and identify reforms to improve the existing system in line with internationally accepted principles. Section 1 gives an overview. Section 2 describes Indonesia's existing public procurement regime and key issues. Section 3 discusses implications of decentralization for public procurement. Section 4 describes the strategy for strengthening fiduciary safeguards in Bank-financed projects based on lessons of experience and findings of the CPAR. From all accounts, the public procurement system in Indonesia does not function well. It is not market-driven, has been prone to misuse and abuse, and reduces value for money for public funds. The report identifies the key reasons why the system does not yet function well. The report suggests the following priority actions toward a reformed procurement process: a) reforming the legal, regulatory, and institutional framework; b) increasing competition; c) improving procedures and practices; d) building professional capacity; e) preparing for decentralization; and f) strengthening enforcement.